Multiple-objective Management based on a Distributed SDN Architecture for Many-cores - Ruaro, Marcelo; Moraes, Fernando (Symposium on Integrated Circuits and Systems Design (SBCCI); 2020: Anais do XXXIII Symposium on Integrated Circuits and Systems Design, 2020)
The management of many-core systems is evolving to meet multiple objectives simultaneously. The Software-Defined Networking (SDN) has benefits explored in recent works that point it as a candidate to address this requirement at the communication level, at the same time that promotes management flexibility and reduced hardware complexity. Most of the research in SDN for many-cores assumes a centralized SDN (C-SDN) Controller and single-objective management This work proposes multi-objective management based on a distributed SDN (D-SDN) architecture (SELF-SDN). The management is self-adaptive, addressing QoS and fault-tolerance simultaneously at the communication level. Experiments targeting QoS show that SELF-SDN provides a reduced amount of latency misses (−67%) and fast reaction time (−49.6%) to recover the QoS constraints compared to a C-SDN approach. Fault-tolerance experiments highlight the simplicity of the SDN paradigm to recover from faults in the NoC, not requiring additional hardware. Results related to multi-objective management demonstrate the fast reaction time of SELF-SDN to recover the communication latency faced to QoS loss and faults, reducing, on average, in 43% the reaction time compared to a C-SDN approach.